2010
DOI: 10.1029/2010ja015849
|View full text |Cite
|
Sign up to set email alerts
|

Waves at the electron plasma frequency associated with solar wind magnetic holes: STEREO/Cluster observations

Abstract: [1] Magnetic depressions are common structures of the interplanetary medium. These magnetic holes can be just isolated dips of the amplitude of the field or they can be associated with discontinuities in the field orientation (tangential or rotational). Electrostatic waves at the plasma frequency (Langmuir waves) are often observed in these magnetic structures. The aim of the present paper is to provide the main characteristics of these waves and to propose a mechanism to explain their formation. The study is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 52 publications
3
24
0
Order By: Relevance
“…Through a multispacecraft analysis using Helios 1 and 2 and Voyager 2 spacecraft data, Sperveslage et al (2000) 10.1029/2019JA027198 investigated the heliocentric radial dependence of MH occurrence rate between 0.3 and 17 AU. Other studies at 1 AU have reported ∼39% of all MHs are of linear type (Briand et al, 2010;Stevens & Kasper, 2007), while over the solar poles, nearly half of the magnetic depressions are linear MHs (Fränz et al, 2000;Tsurutani et al, 2011). Out of 850 MHs in the Sperveslage et al (2000) study, nearly 30% were linear holes, a rate much higher than the 13% rate observed in Ulysses data in the ecliptic plane (Tsurutani et al, 2009).…”
Section: Introductionmentioning
confidence: 57%
“…Through a multispacecraft analysis using Helios 1 and 2 and Voyager 2 spacecraft data, Sperveslage et al (2000) 10.1029/2019JA027198 investigated the heliocentric radial dependence of MH occurrence rate between 0.3 and 17 AU. Other studies at 1 AU have reported ∼39% of all MHs are of linear type (Briand et al, 2010;Stevens & Kasper, 2007), while over the solar poles, nearly half of the magnetic depressions are linear MHs (Fränz et al, 2000;Tsurutani et al, 2011). Out of 850 MHs in the Sperveslage et al (2000) study, nearly 30% were linear holes, a rate much higher than the 13% rate observed in Ulysses data in the ecliptic plane (Tsurutani et al, 2009).…”
Section: Introductionmentioning
confidence: 57%
“…While reported some Langmuir waves at individual discontinuities (25%), most Langmuir waves reported (75%) were associated with depressions in the overall magnetic field strength bounded by a pair of discontinuities, often called magnetic holes. Beam instabilities are thought to be excited at magnetic holes due to a combination of adiabatic motion and timeof-flight effects acting on strahl electrons as they traverse the bounding discontinuities Briand et al, 2010]. However, few of the CSs with nearby ESWs identified in the current study are positively identified as magnetic holes.…”
Section: Discussionmentioning
confidence: 73%
“…In a recent study Briand et al (2010) have shown that the polarization of the waves is compatible with Langmuir/z-mode waves. Through combined observations of STEREO and CLUSTER they have also demonstrated that the presence of a pronounced electron strahl is required for the generation of Langmuir waves and that the electron distribution function inside the magnetic hole is more isotropic compare to outside the hole.…”
Section: Langmuir Waves: From Linear To Nonlinear Plasma Physicsmentioning
confidence: 89%